Pembelajaran Bahasa Mandarin di Masa Orde Baru - Jonathan, Miguel Angelo (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2022)
Mandarin Chinese language has become one of the most popular foreign languages in Indonesia and is taught from kindergarten to university level. Learning Mandarin from the past until now has experienced various developments in conditions. This paper aims to describe the conditions of learning Mandarin in the New Order era. The research method used is a qualitative research method with a historical approach. In collecting data, researchers used the method of documentation. Data sources include newspaper articles, books, and other relevant documents. The results showed that in the New Order era, Mandarin in particular and Chinese culture in general experienced strict restrictions. This is related to the anti-communism campaign and the assimilation policy implemented by the New Order government against the ethnic Chinese community. This policy caused the learning of Mandarin at that time to be halted and could only be studied in a limited way. The results of this study are expected to describe the condition of learning Mandarin in Indonesia during the New Order era and its impact on learning Mandarin in Indonesia at this time.